Mandapa (pillared hall) of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The view of the interior of the mandapa (pillared hall) of Neelkanth Mahadev Temple as seen from the north western corner of the mandapa. In front of the three shrines of this temple is a shared mandapa with four pillars at the centre.